The Case for a Pedagogy for the Oppressor: Race and Social Justice Education In the Context of Post-Apartheid South Africa. - Davis, Danya (Department of Sociology, 2024)
Nearly two decades following the end of political apartheid racial inequality in South Africa is ever-present. Many young South Africans struggle with both the country's history and present realities. Universities offer a unique opportunity to empower students to become engaged and contributing members of society. This research was inspired by my own experiences with engaging issues of social justice, race and whiteness. I began by asking, "What pedagogical approach is most likely to shift white students and assist them in becoming allies to social justice?" My search for an answer led me to writing this theory-based thesis in which I use secondary references to support the argument for the implementation of a Pedagogy for the Oppressor in privileged social justice-oriented South African university classrooms. I summarise Post-Conflict Pedagogy as written about by Jonathan Jansen, and Pedagogy for the Oppressor as articulated by Rick Lee Allen, contrasting these two approaches in an effort to show the ideological contestations in the field. While both pedagogies aim towards creating a racially . just and inclusive society, they differ in how educators must best engage students in order to create such a society. I argue against Post-Conflict Pedagogy which is opposed to the use of critical theory and critical pedagogy - pedagogical frames which name oppression and oppressors - in the South African context. The pedagogy gives preference to indirect methods while promoting • safe space and encouraging the use of dialogue and personal experience. Pedagogy for the Oppressor encourages educators to understand and challenge the ways that white students resist social justice education. It requires challenging oppressor students to do their share of the race work by owning their role in both perpetuating and challenging oppression; it requires intervening in student resistance in firm yet tender ways employing "radical love" in a way that simultaneously offers both challenge and support. Pedagogy for the Oppressor involves speaking truth to power in ways that are neither comfortable nor easy. I consider what implementing this pedagogy requires with specific reference to the re-conceptualising of resistance and safety, and problematize the unchallenged use of dialogue and personal experience in the social justice classroom. Pedagogy for the Oppressor involves challenging typical resistant discourses and understanding how oppressor students use emotions to derail the pedagogical space. As such I explore the role of fear, anger, guilt and empathy, highlighting how these emotions are problematically embodied and where relevant how they can be embodied more usefully. Firm pedagogies that deconstruct white ways of knowing and being must be matched with inviting students to start the lifelong journey towards becoming allies to social justice and showing white students alternative, social justice-oriented ways of being, knowing and behaving. I explore what this allied identity might entail concluding that it requires a commitment to social justice for all, that is embedded in race and power consciousness. Furthermore, knowledge and reflection are required before action is engaged, least well intentioned actions further reproduce oppression.